Political corruption - Young, Mitchell (Farmington Hills, MI : Greenhaven Press, 2009)
Essays debate issues of political corruption in the United States, including claims of executive privilege, independent counsel, campaign financing limits, and the role of the federal government in prosecuting local corruption.
Political corruption and the abuse of executive privilege -- The Independent Counsel as a tool against corruption -- Fighting corruption by limiting campaign spending and contributions -- Expanding the federal government's right to prosecute local corruption.
Keywords: Political corruption -- United States